Reception at very large distances of monochromatic Rayleigh wave of the 2018–2019 Mayotte crisis: attenuation factor of Ms magnitude - Talandier, Jacques (Comptes Rendus. Géoscience, 2024)
During the strong 2018 and 2019 submarine volcano-seismic events on the Fani Maoré volcano on the eastern flank of the island of Mayotte (Indian Ocean), numerous unusual long-period monochromatic Rayleigh wave trains (VLPs) were recorded. Similar perfectly monochromatic signals but with much lower intensities were previously observed in 2011, 2013 and 2017 from the Rocard submarine volcano (Society hot spot, French Polynesia). The VLPs of Mayotte and Rocard are the only signals of this type observed so far. Perfectly monochromatic and recorded up to the antipodes, the Rayleigh wave trains of Mayotte allow verifying experimentally the attenuation factor of the Ms magnitude scale, thus justifying the reception of these signals from sources of modest energy at very large distances.